The Effect Of Quarter-Wave Transformer Matching Network To The X-Circular Polarized Antenna - Abd Aziz, Mohamad Zoinol Abidin; Ahmad Mufit, Nur Alyaa Diyana; Suaidi, Mohamad Kadim; Rahim, M. K. A. (Penerbit Universiti, UTeM, 2013)
This technical paper presents the 2 design of xcircular polarized with slanted rectangular slot microstrip patch antenna by using single port in X-form is at 45 0 , 135 0 , 225 0 and 315 0 . The combination of 4 circular patches of Design 1 and the additional of quarter wave impedance matching technique for Design 2 have been used to design the X-circular polarized with slanted rectangular slot microstrip patch antenna. The designs are simulated using Computer Simulation Technology (CST) with dielectric constant, εr =4.3 and tan δ=0.019 and thickness of substrate, t=1.6mm. The simulation results such as return loss, bandwidth, gain, directivity and polarization have been compared